To solve the equation for y, we need to isolate y on one side of the equation.
Starting with:
2x + 3y = -12
Subtract 2x from both sides:
3y = -2x - 12
Now divide both sides by 3:
y = (-2x - 12)/3
So the equation for y is y = (-2x - 12)/3.
Solve the equation for `y`:
`2x+3y=-12`
3 answers
try again.
Apologies for the mistake.
To solve for y, let's isolate it on one side of the equation.
Starting with:
2x + 3y = -12
Subtract 2x from both sides:
3y = -2x - 12
Divide both sides by 3:
y = (-2x - 12)/3
Therefore, the equation for y is y = (-2x - 12)/3.
To solve for y, let's isolate it on one side of the equation.
Starting with:
2x + 3y = -12
Subtract 2x from both sides:
3y = -2x - 12
Divide both sides by 3:
y = (-2x - 12)/3
Therefore, the equation for y is y = (-2x - 12)/3.